Building a Better Future Together : Dominican Republic Policy Notes - World Bank Group (World Bank, Washington, DC, 2017)
In preparing these policy notes, the World Bank intends to provide the incoming administration with some considerations and recommendations on key development policy issues. The focus of these policy notes is on the challenges that need to be overcome and the policy options that can be pursued to keep the Dominican Republic on a path of sustainable and inclusive growth. The sectors and thematic areas covered in the policy notes include: (i) recent trends in poverty and shared prosperity; (ii) the quality and coverage of public spending on the social sectors (education, health, and social protection); (iii) an assessment of the factors that can affect the quality and efficiency of infrastructure services in the sectors of water and sanitation, and electricity; and (iv) the factors that can affect the sustainability of growth from an economic, social, and environmental and climate resilience points of view. Each policy note describes succinctly the current country context, what the existing main challenges are in each sector, and what the focus of policy should be to secure sustainable and inclusive growth.